Penciptaan Busana Ready to Wear Deluxe dengan Sumber Ide Rumah Adat Suku Tengger - Anggun Ica Maydasari; Imami Arum Tri Rahayu; Inty Nahari; Lutfiyah Hidayati (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This creative research aims to produce deluxe ready-to-wear fashion by elevating local culture into modern fashion designs that have aesthetic and exclusive value. The main focus of the creation is to enrich the variety of Indonesian culture-based fashion designs through a practice-led research approach. The traditional house of the Tengger Tribe was chosen as the main source of ideas because of its unique architectural form and the philosophical values contained therein, which are still rarely explored in the fashion world. The creation process consists of four stages, namely: exploration of the source of ideas, design, realization of the work, and presentation of the work. In the exploration stage, visual studies and literature studies were conducted regarding the visual characteristics and philosophy of the traditional house of the Tengger Tribe. Next, these ideas were translated into fashion designs with an artistic and functional approach. The resulting works are three ready-to-wear deluxe characters, consisting of two women's outfits and one men's outfit. The techniques used in the realization process include semi-couture and fabric manipulation with stylized embroidery applications that represent the architectural elements of the traditional Tengger house. The results of the work were presented in a theatrical fashion show with the theme